ANALISIS KINERJA KEUANGAN PT MEDIKALOKA HERMINA TBK DAN IMPLIKASINYA TERHADAP EKSPANSI PERUSAHAAN - Alexius Imanuel; Featy Octaviany (POLITEKNIK LP3I JAKARTA, 2026)
This study aims to analyze the financial performance of PT Medikaloka Hermina Tbk and examine its implications for hospital expansion capability by comparing it with PT Siloam International Hospitals Tbk. The research employs a descriptive quantitative approach using financial ratio analysis, which includes liquidity, solvency, and profitability ratios based on the companies’ financial statements for the 2020–2024 period. The data used in this study are secondary data obtained from published annual financial reports. The results indicate that the financial performance of PT Medikaloka Hermina Tbk is generally stable, with relatively strong liquidity, solvability and profitability levels that support the company’s hospital expansion strategy. Meanwhile, PT Siloam International Hospitals Tbk demonstrates strong capabilities in asset management and capital structure, although it presents different financial characteristics. The comparison of the two companies suggests that sound financial performance plays a significant role in supporting the sustainability of hospital network expansion. Therefore, effective and efficient financial management is essential to enhance the company’s capacity to expand healthcare services to the community.